Philosophy of Ayam Jago: Researching The Values of Character Education in Customary Perbayo Sungai Tutung Village, Kerinci District - Muhamad Yusuf; Nuzul Iskandar; Doli Witro; Ogi Sandria (Jurnal Dialog, 2021)
Perbayo is a speech delivered at the coronation ceremony of a local village leader that embraces three aspects, namely: the creation of human, the Kerinci’s natural history, and the leadership. As for the third aspect, the values are often analogous to a rooster having six characters: 1) langsing kokok (good crow); 2) sibar ekor (beautiful tail); 3) kembang sayap (wide wings); 4) besar paruh (big beak); 5) lebar dada (big chest); and 6) runcing taji (sharp spur). The six characters are metaphors of the values that a leader of Sungai Tutung Village must have. This study aims to explore the practice of character education among the people of Sungai Tutung Village. Using a semi-ethnographic design, this study found: firstly, the rooster’s six characters symbolize leadership values that have been preserved from generation to generation among the customary leaders of Sungai Tutung Village; secondly, the analogy of the rooster is maintained because apart from being easy to remember, it symbolizes courage, dignity, wisdom, and responsibility. Perbayo merupakan pidato saat penobatan pemuka adat desa yang memiliki penekanan pada tiga aspek, yaitu penciptaan manusia, sejarah alam Kerinci, dan kepemimpinan. Pada aspek ketiga, nilai-nilainya seringkali dianalogikan dengan ayam jago yang memiliki enam karakter: 1) langsing kokok; 2) sibar ekor; 3) kembang sayap; 4) besar paruh; 5) lebar dada; dan 6) runcing taji. Keenam karakter tersebut adalah metafor dari nilai-nilai yang mesti hidup dan tumbuh dalam individu pemuka adat di Desa Sungai Tutung. Artikel ini bertujuan untuk menggali nilai-nilai pendidikan karakter yang terdapat dalam Perbayo Adat Desa Sungai Tutung. Dengan menggunakan desain semi etnografi, studi ini menemukan: pertama, enam karakter ayam jago merupakan nilai-nilai kepemimpinan yang dilestarikan secara turun-temurun oleh pemuka adat Desa Sungai Tutung; kedua, analogi ayam jago dipertahankan karena selain gampang diingat dan disebut, ayam jago menyimbolkan keberanian, kewibawaan, kebijaksanaan, dan bertanggungjawab.